Assessing the Influential Factors Associated with Medication Non-Adherence and Self-Care Practices Among Type 2 Diabetes Mellitus Patients in Tripoli, Libya (Sciences of Pharmacy, 2023)
Influential factors causing poor adherence to antidiabetic medications and self-care practices among type 2 diabetes mellitus (T2DM) patients have not been reported before in Libya. To assess such factors that contribute to non-adherence, a single health facility, cross-sectional descriptive study was carried out on T2DM patients attending the NCDE in Tripoli/ Libya; using a pre-tested questionnaire. Crude odds ratios in the binary logistic regression were used to describe the associations between medication adherence and various independent factors using SPSS version 26. Adjusted odds ratios with their corresponding 95% confidence intervals were further generated in the multivariable analysis, to determine variables which were independently associated with medication adherence and were considered significant at a p-value of <0.05. Of the 380 study participants, only 225(67.1%) were adherent. 159(41.8%) were non-adherence to physician recommendations and were careless when taking their medication, 200(52.6%) found difficulty maintaining recommended dietary restrictions, 211(55.5%) and 97(25.5%) didn’t adhere to regular exercise or blood glucose monitoring; respectively. Factors significant association with non-adherence were; medication being taken; especially patients who were prescribed OHA and insulin ([AOR] [95% CI] = 0.214[0.073-0.632]), being careless and not taking prescribed medication as recommended ([AOR] [95% CI] = 2.880 [1.387- 5.983]), forgetfulness ([AOR] [95% CI] =0.199 [0.070- 0.570], stop taking prescribed antidiabetic medication when feeling well ( [AOR] [95% CI] = 0.153[0.058- 0.402], medications side effects ( [AOR] [95% CI]=0.382 [0.181- 0.809] and unawareness of the consequences of not adhering to medication as recommended and the consequences skipping doses ([AOR] [95% CI] = 0.146 [0.037- 0.581]). Adherence to recommended medication and self-care practices in Libya is unsatisfactory. Diabetes education, awareness programs, and regular monitoring of T2DM individuals’ medication adherence and self-care practices are vitally required.